MANDAT REKONSILIATIF SEBAGAI TANGGUNG JAWAB SOSIAL POLITIK PENDIDIK KRISTEN - Mulyo Kadarmanto (Manna Rafflesia, 2019)
This paper aims to formulate a form of social political responsibility of Christian educators based on the work of reconciliation that was carried out by the Lord Jesus in his work of death and resurrection. By looking at the socio-political situation of the Indonesian people who are currently vulnerable to splitting with ethnic, religious and racial issues. This identity politics is used as a tool to gain victory in political battles. As Christian educators who are part of citizens and must contribute to the peace and tranquility of the Indonesian nation, Christian educators are indeed important to reflect on reconciliation work that is able to create peace, so that with this foundation the presence of Christian educators can neutralize the social political situation and can even be actively involved in uniting various parties both in the context of class and society.